Infeksi Plasmodium berghei dan Kesannya Keatas pengisyaratan MAP Kinase Eritrosit Perumah - Mohd.Fakharul Zaman Raja Yahya, -; Hasidah Mohd sidek, - (Universiti Kebangsaan Malaysia, 2009)
The present investigation involves monitoring the development of parasitemia and the distribution of Plasmodium berghei morphologies during parasite infection in mice as well as the effect P. berghei infection on MAP kinase signaling in its erythrocyte host. Microscopic analyses of Giemsa-stained blood films prepared from P. berghei (strain PZZ1/00)-infected mice showed that the level of parasitemia reached up to 70% two weeks after inoculation of the parasite. Parasite ring and trophozoite forms were clearly detected in the blood films throughout the study period while the schizont form was visibly observed on day 3 post-inoculation. Western blotting [primary antibody: monoclonal anti-MAP kinase (non-phosphorylated ERK-1/2); secondary antibody: HRP-conjugated polyclonal anti-IgG] carried out on SDS-PAGE-separated cytosolic protein samples from P. berghei-infected (70% parasitemia) erythrocytes showed that the levels of both 42 and 44 kDa MAP kinase-immunoreactive proteins increased significantly (p<0.05) at 70% parasitemia, by up to 21.5% and 22.3% respectively as compared to non-infected control samples. Whether the effect of P. berghei infection at 70% parasitemia on host MAP kinase signaling is related to the MAP kinase activation remains to be further investigated